2020
DOI: 10.3892/etm.2020.9379
|View full text |Cite
|
Sign up to set email alerts
|

Sophocarpine attenuates septic liver injury through suppression of the NLRP3 inflammasome via autophagy‑mediated degradation

Abstract: Septic liver injury remains a challenge in sepsis treatment. Nucleotide-binding oligomerization domain, leucine rich repeat and pyrin domain containing 3 (NLRP3) inflammasome activation has been suggested to be a major cause of hepatocyte cell death in liver diseases. However, insufficient research has been performed to explore the underlying mechanisms associated with this. In the present study, sophocarpine, a pharmaceutical monomer originally isolated from Sophora flavescens, was suggested to attenuate sept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…NOD-like receptor family pyrin domain-containing 3 (NLRP3) inflammasomes can stimulate the inflammation and induce immune cell apoptosis to exacerbate the development of sepsis [ 11 ]. Moreover, inactivation of NLRP3 inflammasomes could alleviate septic liver injury through autophagy-mediated degradation [ 12 ]. As previously reported, pyroptosis induced by the NLRP3/caspase-1 pathway could affect cognitive deficits in mice with sepsis-related encephalopathy [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NOD-like receptor family pyrin domain-containing 3 (NLRP3) inflammasomes can stimulate the inflammation and induce immune cell apoptosis to exacerbate the development of sepsis [ 11 ]. Moreover, inactivation of NLRP3 inflammasomes could alleviate septic liver injury through autophagy-mediated degradation [ 12 ]. As previously reported, pyroptosis induced by the NLRP3/caspase-1 pathway could affect cognitive deficits in mice with sepsis-related encephalopathy [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, inactivation of NLRP3 inflammasomes could alleviate septic liver injury through autophagy-mediated degradation [ 12 ]. As previously reported, pyroptosis induced by the NLRP3/caspase-1 pathway could affect cognitive deficits in mice with sepsis-related encephalopathy [ 12 ]. Additionally, NLRP3-dependent caspase-1/11-GSDMD pathway was previously demonstrated to mediate pyroptosis in the hippocampus of a sepsis model [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The content of matrine and oxymatrine, the characteristic components of S. tonkinensis , is specified in Pharmacopoeia of the People's Republic of China (Pharmacopoeia of People's Republic of China, 2020). Modern pharmaceutical studies showed alkaloids such as cytisine, matrine, oxymatrine, and sophocarpine have displayed different biological activities, including antiviral (Ding et al, 2006), antipyretic (Cho et al, 1986), anti‐inflammatory (He et al, 2019; Hou et al, 2020), and hepato‐protective activities (Huang & Xu, 2020; Wan et al, 2009). Meanwhile, alkaloids in S. tonkinensis were found to exhibit toxicity (Li, Zhao, et al, 2021; Wang et al, 2017; Wang, Wang, et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The residue was redissolved in 200 μL of 80% methanol, and the supernatant was transferred into the UPLC sample vial for LC-MS analysis. et al, 2006), antipyretic (Cho et al, 1986), anti-inflammatory (He et al, 2019;Hou et al, 2020), and hepato-protective activities (Huang & Xu, 2020;Wan et al, 2009). Meanwhile, alkaloids in S. tonkinensis were found to exhibit toxicity (Li, Zhao, et al, 2021;Wang et al, 2017;.…”
Section: Pretreatment Of Biological Samplesmentioning
confidence: 99%
“…Impairing acute hepatic autophagy activation via local genetic inactivation worsened hepatic mitochondrial damage/dysfunction and aggravated liver damage after CLP in mice [35]. In other CLP mouse studies, autophagy enhancement alleviated liver injury [36,37]. Autophagy regulation protects against liver injury evoked by liver surgery associated ischemia-reperfusion [38].…”
Section: Key Pointsmentioning
confidence: 98%